Fate of the fecal indicator Escherichia coli in irrigation with partially treated wastewater. (15th November 2015) - Vergine, P.; Saliba, R.; Salerno, C.; Laera, G.; Berardi, G.; Pollice, A.
Abstract: Treated wastewater reuse is increasing in semi-arid regions as a response to the effects of climate change and increased competition for natural water resources. Investigating the fate of bacterial indicators is relevant to assess their persistence in the environment and possible transfer to groundwater or to the food chain. A long-term field-scale experimental campaign and a soil column test were carried out to evaluate the fate of the fecal indicator Escherichia coli ( E. coli ) in a cultivated soil when contaminated water resources are used for irrigation. For field experiments, fecal contamination was simulated by dosing the indicator to the effluent of a membrane bioreactor, thus simulating a filtration system's failure, and irrigating a test field where grass was grown. The presence of E. coli on grass and topsoil samples was monitored under different scenarios. For evaluating the fate of the same indicator in the subsoil, a set of soil columns was installed next to the field, operated, and monitored for E. coli concentration over time and along depth. Real municipal wastewater was used in this case as source of fecal contamination. Results showed that short- and medium-term effects on topsoil were strongly dependent on the concentration of E. coli in the irrigation water. Limited persistence and no relevant accumulation of the indicator on the grass and in the topsoil were observed. Watering events performed after fecal contamination did not influence significantly the decay in the topsoil, which followed a log-linear model. The trend of the E. coli concentrations in the leaching of the soil columns followed a log-linear model as well, suggesting bacterial decay as the dominant mechanism affecting the underground indicator's concentration. Graphical abstract: Highlights: Fate of Escherichia coli after irrigation with contaminated water was assessed with field and soil column tests. E. coli concentration in irrigation water mainly influences short-term soil contamination. Dye-off is the dominant process affecting E. coli concentration in topsoil and leaching water. Persistence models of E. coli in topsoil and leachate after pollution are log-linear. Less than 1% of E. coli in irrigation water is transferred through the soil column.